Cancer Incidence and Mortality in Changzhou City, Jiangsu Province, 2015 - LUO Wenshu (Zhongliu Fangzhi Yanjiu, 2020)
Objective To analyze the incidence and mortality of cancer in Changzhou city, Jiangsu Province, China in 2015, to provide important data for the study of prevention and control strategy of cancers. Methods Based on the data of cancer registration and follow-up in Changzhou city in 2015, we calculated the crude incidence/mortality rates, the age-specific incidence/mortality rate, age-standardized incidence/mortality, cumulative incidence/mortality rate (0-74 age years old) as well as the rank and the constitution of top 10 cancers. The age-standardized incidence/mortality was calculated and adjusted by the Chinese population census in 2000. Results A total of 13419 new cancer cases in 2015 were collected. The crude incidence of cancer was 361.78/105, and the age-standardized incidence was 259.58/105 in total population, 283.44/105 in males and 232.35/105 in females. The mortality of cancer was 218.48/105, and the age-standardized mortalities were 145.65/105 in total population, 183.99/105 in males and 104.69/105 in females. The incidence of gastric cancer ranked the first, followed by lung cancer, colorectal cancer, esophageal cancer and liver cancer. The incidence of gastric cancer ranked the first in males, and breast cancer ranked the first in females. The mortality of lung cancer ranked the first in both males and females. Conclusion The incidence and mortality of malignant tumors are relatively high in Changzhou city. We should explore the appropriate prevention methods to reduce the cancer incidence and mortality in Changzhou city.